Transcriptome Analysis Identifies Novel Mechanisms Associated with the Antitumor Effect of Chitosan-Stabilized Selenium Nanoparticles - Hector Estevez; Estefania Garcia-Calvo; Jose Rivera-Torres; María Vallet-Regí; Blanca González; Jose L. Luque-Garcia (MDPI AG, 2021)
Selenium nanoparticles (SeNPs) have been receiving special attention in recent years due to their antioxidant capacity and antitumor properties. However, the mechanisms associated with these properties remain to be elucidated. For this reason, a global transcriptome analysis has been designed in this work and it was carried out using human hepatocarcinoma cells and chitosan-stabilized SeNPs (Ch-SeNPs) to identify new targets and pathways related to the antitumor mechanisms associated with Ch-SeNPs. The results obtained confirm the alteration of the cell cycle and the effect of Ch-SeNPs on different tumor suppressors and other molecules involved in key mechanisms related to cancer progression. Furthermore, we demonstrated the antioxidant properties of these nanoparticles and their capacity to induce senescence, which was further confirmed through the measurement of β-galactosidase activity.